Workarounds to Intended Use of Health Information Technology: A Narrative Review of the Human Factors Engineering Literature. (May 2018) - Patterson, Emily S.
Objective: To integrate and synthesize insights from recent studies of workarounds to the intended use of health information technology (HIT) by health care professionals. Background: Systems are safest when the documentation of how work is done in policies and procedures closely matches what people actually do when they are working. Proactively identifying and managing workarounds to the intended use of technology, including deviations from expected workflows, can improve system safety. Method: A narrative review of studies of workarounds with HIT was conducted to identify themes in the literature. Results: Three themes were identified: (1) Users circumvented new additional steps in the workflow when using HIT, (2) interdisciplinary team members communicated via HIT in text fields that were intended for other purposes, and (3) locally developed paper-based and manual whiteboard systems were used instead of HIT to support situation awareness of individuals and groups; an example of a locally developed system was handwritten notes about a patient on a piece of paper folded up and carried in a nurse's pocket. Conclusion: Workarounds were employed to avoid changes to workflow, enable interdisciplinary communication, coordinate activities, and have real-time portable access to summarized and synthesized information. Application: Implications for practice include providing summary overview displays, explicitly supporting role-based communication and coordination through HIT, and reducing the risk to reputation due to electronic monitoring of individual performance.